Fihrist-i asnad-i Tarikhi-i Vizarat-i Umur-i Kharijah, dawran-i Qajariyah / . List of Foreign Ministry's historical documents (Vizarat-i Umur-i Kharijah. Idarih-i Intishar-i Asnad va Archiv)
2 : 1220-1222 h.q. - 362 p.